Rare Presentation of Self-Limiting Kikuchi–Fujimoto Disease in Relapsing Nature - Karo Servatyari; Hero Yazdanpanah; Chamara Dalugama (Case Reports in Medicine)
Background. Kikuchi–Fujimoto disease (KFD) is a rare, benign, and self-limiting disease that is commonly associated with cervical lymphadenopathy and fever. The disease has a wide spectrum of clinical manifestations, and definitive diagnosis is based on the histological appearance in the excision biopsy of the lymph nodes. Recurrence of KFD is reported rarely. Case Presentation. A 56-year-old Iranian woman with a background history of thrombocytopenia presented with fever, malaise, loss of appetite, and weight loss with cervical lymphadenopathy. The excision biopsy of the cervical lymph nodes confirmed the diagnosis of KFD, and she made a full recovery with improvement of symptoms, regression of cervical lymph nodes, and normalization inflammatory markers. One year after remission, she presented with similar clinico-biochemical profile, and repeat biopsy confirmed KFD. Conclusion. Although the rate of recurrence of the disease is very low, the treating physician should consider the possibility and confirm it histologically.